Zamek w Radziejowie w świetle badań terenowych 1987 roku - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1991)
The subject of the present article is to present the results of research archaeological work in the castle of Radziejów in Kujawy (province of Włocławek) led by the team workers of Archaeological Institute of University of Łódź in 1987. Relics of Radziejów castle are not preserved at present. On the plan of the town caning from 1820 there are no buildings but only round, tumular, surrounded by a ditch, earthen moud which was localized in the eastern part of the town. Fairly detailed desaiptions of buildings of the castle come from the inspection of royal lands of Brześć-Kujawy province in 1616, 1628-1632, 1767 and 1777. This year’s field studies were of veryfying character and were to answer the question: what is the stale of cultural layers and hidden under ground relics of castle buildings? Due to the complete building up of the area and since it was impossible to localize research excavations there only 3 sounding excavations of 2.0x3.0 m size were marked out. Besides them 35 bore-holes by means of geological hand-chill were made. In 3 bore-holes the surrounding trough was recorded. The cultural layers of the middle part of court-yard was examined in the excavation no 1. The complete destrucion of levels of the castle related to the levelling of the ground in the first half of the XX century was observed in the excavation no 2; in the excavation no 3 almost 4 m high stratification of the approaches of the castle. In this excavation besides a quite large set of relics, 6 fragments of day vessels ornamented with Late-Gothic signs which should benrelated to traditions of Hussite movement which were vivid in Kujawy in the half of the XV century. The confrontation of results of field works with written sources allowed us to accept the following hypothesis reflecting the rhythm of development of Radziejów castle. The castle, at the beginning only periodycaly visited royal station, was founded probably on the turn of the XV century. In that phase it was not "a castle" but-rather "a manor-house" situated near the town. As late as the beginning of the XVI century in the time of Radziejów starosty held by a powerful family of Leszczyński, a stone tower and a wooden house of "registry" used for collecting court records and also other wooden buildings were constructed. At that time, most likey the moud was fonded and surrounded with a wooden fence. In the half of the XVII century Radziejów castle was burnt by the Swedish Soldiers and began to fall into decay. As early as the second half of the XVIII century it was ruined and the remains of walls of the castle were pulled down before 1820. This year’s archaeological investigations proved that the area occupied by the castle is to a great extent destroyed mostly due to the lowering of the mound on the turn of twenties and thirties of the XXth century and erecting new buildings. It was concluded that further investigations should be led by historians rather than archaeologists.